Podnikatelský plán pro rozvoj malého podniku - Vantroba, Štefan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Cielom tejto diplomovej prace je navrhnut podnikatelsky plan na rozvoj malej firmy. V prvej casti je teoreticky opisane prostredie malych firiem. Dalej je skumane obchodne prostredie firmy a adopcia praktik riadenia vztahu so zakaznikmi (CRM) v oblasti malych firiem. V poslednej casti autor navrhuje podnikatelsky zamer jednoduchej webovej CRM sluzby Zakaznici.eu a detailnejsie specifikuje projekt rozvoja.

The aim of this diploma thesis is to propose a business plan for development of small business. First part introduces small business from a theoretical perspective. Next the company and its business environment is assessed and an adoption of customer relationship management practices (CRM) and software among small businesses is examined. In the last part author proposes new business plan for simple CRM web service Zakaznici.eu and further specifies the development of a project.
Business Plan for Small Business Development
Keywords: Drobne podnikanie; maly podnik; podnikatelsky zamer; podnikatelsky plan; CRM; riadenie vztahu so zakaznikmi; Small business; business development; business plan; SWOT analysis; CRM; customer relationship management